1990
DOI: 10.1161/01.res.67.6.1525
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic agonists stimulate the oxidative pentose phosphate pathway in the rat heart.

Abstract: The oxidative pentose phosphate pathway is poorly developed in the rat heart compared with other organs, since the activity of glucose-6-phosphate dehydrogenase (G-6-PDH), the first and rate-limiting enzyme of the oxidative pentose phosphate pathway, is low. As a consequence, the available pool of 5-phosphoribosyl-1-pyrophosphate and the rate of adenine nucleotide biosynthesis are limited. Isoproterenol, 24 hours after subcutaneous administration at 0.1, 1, and 25 mg/kg, stimulated the activity of G-6-PDH in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In fact, the isoproterenol-induced prolonged enhancement of cardiac adenine nucleotide biosynthesis appears to be maintained by this elevation in PRPP. 4 Moreover, both isoproterenol3 and NE induced cardiac hypertrophy that could be prevented by 8-adrenergic3 and combined a-and P3-adrenergic'3 blockade, respectively ( Table 2). …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, the isoproterenol-induced prolonged enhancement of cardiac adenine nucleotide biosynthesis appears to be maintained by this elevation in PRPP. 4 Moreover, both isoproterenol3 and NE induced cardiac hypertrophy that could be prevented by 8-adrenergic3 and combined a-and P3-adrenergic'3 blockade, respectively ( Table 2). …”
Section: Resultsmentioning
confidence: 97%
“…13-Adrenergic stimulation with isoproterenol increased cardiac G-6-PD activity, the available PRPP pool, and adenine nucleotide biosynthesis. 4 More recently, a-adrenergic stimulation of the heart has attracted much attention. It has been shown that inositol 1,4,5-trisphosphate (IP3) and diacylglycerol are second messengers7 and that the increase in 1P3 precedes the positive inotropic effect in isolated heart preparations obtained from rats8 and humans.9 Moreover, a-adrenergic stimulation has been identified as one of the possible trigger mechanisms for the induction of myocardial cell growth both in cultured neonatal rat cardiac myocytes10-12 and in rats in vivo.13 ADP UDP 4 4 ATP UTP FIGURE 1.…”
mentioning
confidence: 99%
“…We show that adrenergic-deficient embryos have decreased G-6-PDH activity, increased ratios of phosphorylated to total G-6-PDH protein, and decreased ribose-5-phosphate, PRPP, and nucleotide concentrations indicating G-6-PDH and PPP are effectively regulated by adrenergic stimulation during embryonic development. Other studies have also shown adrenergic regulation of PPP in working rat hearts exposed to NE and other adrenergic agonists with increased G-6-PDH activity, PRPP concentrations, and adenine nucleotide biosynthesis (59)(60)(61). During development, G-6-PDH has been shown to be protective against oxidative stress resulting from placental circulation and nutrient/respiratory exchange (31,38).…”
Section: Glucose-6-phosphate Dehydrogenase (G-6-pdh)mentioning
confidence: 92%
“…One study shows that P-adrenergic agonists increase the oxidative pentose phosphate pathway and that the P-adrenergic antagonist atenolol reduces the agonist-induced increase (73). This suggests that propranolol might also have a reducing effect on pentose shunt activity.…”
Section: Saccharomyces Cerevisiae and Candida Uti/is Compared By The mentioning
confidence: 99%